Circulating microRNAs and treatment response in the Phase II SWOG S0925 study for patients with new metastatic hormone‐sensitive prostate cancer. Issue 2 (6th November 2017) - Cheng, Heather H.; Plets, Melissa; Li, Hongli; Higano, Celestia S.; Tangen, Catherine M.; Agarwal, Neeraj; Vogelzang, Nicholas J.; Hussain, Maha; Thompson, Ian M.; Tewari, Muneesh; Yu, Evan Y.
Abstract : Background: Previous studies suggest circulating, blood‐based microRNAs (miRNAs) may serve as minimally invasive prostate cancer biomarkers, however there is limited data from prospective clinical trials. Here, we explore the role of candidate plasma miRNAs as potential biomarkers in the SWOG 0925 randomized phase II study of androgen deprivation combined with cixutumumab versus androgen deprivation alone in patients with new metastatic hormone‐sensitive prostate cancer. Methods: Correlative biospecimens, including circulating tumor cells (CTCs) and plasma for miRNA analysis, were collected at baseline and after 12 weeks on treatment from 50 patients enrolled on SWOG 0925. Circulating microRNAs were quantified using real‐time RT‐PCR microRNA array that allowed specific analysis of previously identified candidate miRNAs (miR‐141, miR‐200a, miR‐200b, miR‐210, and miR‐375) as well as discovery analysis to identify new candidate miRNAs. MiRNA levels were correlated to previously reported CTC counts using CellSearch® (Veridex) and with the primary study outcome of 28‐week PSA response (≤0.2, 0.2 to ≤4.0, or >4.0 ng/mL), previously shown to correlate with overall survival. Results: We observed a correlation between baseline circulating miR‐141, miR‐200a, and miR‐375 levels with baseline CTCs. Baseline miR‐375 levels were associated with 28‐week PSA response (≤0.2, 0.2 to ≤4.0, or >4.0 ng/mL, P = 0.007). Using ROC curve analysis, there was no significant difference between baseline miR‐375 and baseline CTC in predicting 28‐week PSA response (≤0.2 vs >0.2 ng/mL). To discover novel candidate miRNAs, we analyzed 365 miRNAs for association with the 28‐week PSA response endpoint and identified new candidate miRNAs along with the existing candidates miR‐375 and miR‐200b ( P = 0.0012, P = 0.0046, respectively. Conclusions: Baseline plasma miR‐141, miR‐200a, and miR‐375 levels are associated with baseline CTC count. Baseline miR‐375 was also associated with the trial endpoint of 28‐week PSA response. Our results provide evidence that circulating miRNA biomarkers may have value as prognostic biomarkers and warrant further study in larger prospective clinical trials.